2008
DOI: 10.1016/j.neulet.2008.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific modulation of PER2 expression in the limbic forebrain and hypothalamus by nighttime restricted feeding in rats

Abstract: Feeding schedules that restrict food access to a predictable daytime meal induce in rodents food-anticipatory behaviors, changes in physiological rhythms and shifts in the rhythm of clock gene expression in the brain and periphery. However, little is known about the effects of nighttime restricted feeding.Previously, we showed that daytime restricted access to a highly palatable complete meal replacement, Ensure Plus (Ensure), shifts the rhythm of expression of the clock protein PER2 in limbic forebrain areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 28 publications
(32 reference statements)
6
37
2
Order By: Relevance
“…This dissociation in the effect of DA on these regions is unusual because the daily patterns of PER2 expression in these regions are synchronized (Amir et al 2004;Lamont et al 2005), and we have previously shown that a number of stimuli that entrain rhythms of clock gene and protein expression, including restricted feeding (Waddington Lamont et al 2007;Verwey et al 2008) and changes in circulating levels of corticosterone , have a consistent effect on the patterns of PER2 in these two regions. The BNSTov and CEA share many anatomical, cellular, and functional characteristics and have been described as components of a larger limbic structure, referred to as the central extended amygdala (Alheid and Heimer 1988).…”
Section: -Ohda Injections Blunt Daily Per2 Patterns In Regions Of Thmentioning
confidence: 84%
“…This dissociation in the effect of DA on these regions is unusual because the daily patterns of PER2 expression in these regions are synchronized (Amir et al 2004;Lamont et al 2005), and we have previously shown that a number of stimuli that entrain rhythms of clock gene and protein expression, including restricted feeding (Waddington Lamont et al 2007;Verwey et al 2008) and changes in circulating levels of corticosterone , have a consistent effect on the patterns of PER2 in these two regions. The BNSTov and CEA share many anatomical, cellular, and functional characteristics and have been described as components of a larger limbic structure, referred to as the central extended amygdala (Alheid and Heimer 1988).…”
Section: -Ohda Injections Blunt Daily Per2 Patterns In Regions Of Thmentioning
confidence: 84%
“…Even so, the daily patterns of circadian clock gene expression are responsive to restricted feeding schedules, and this response is also region specific 57 . For example, restricted feeding schedules that provide daytime or nighttime meals will adjust circadian oscillations in some overlapping brain areas, but some of these effects will also depend on the meal time rather than the restriction, per se 42, 43 . The importance of the circadian time when food is consumed is further emphasized when rodents are fed a high-fat diet during either their active or their inactive period 64 .…”
Section: Sites and Sources Of Circadian Controlmentioning
confidence: 99%
“…These include the DMH (Gooley et al 2006;Mieda et al 2006;Verwey et al 2007Verwey et al , 2008, dorsal striatum and nucleus accumbens (Angeles-Castellanos et al 2007;Verwey and Amir 2011), the cerebral cortex and hippocampus (Wakamatsu et al 2001), the stomach (LeSauter et al 2009), and the liver (Stokkan et al 2001). …”
Section: Oscillators Mediating Anticipation Of Feedingmentioning
confidence: 99%